The Effect Of Dividend Policy (Dpr) And Debt To Equity Ratio On Company Value (Pbv) In The Consumer Non-Cyclicals Sector Companies That Registered In Idx On Period Of 2017-2019 Achmad Fadjar1, Aris Purnama - et. al., Achmad Fadjar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Price to Book Value is one of the variables considered by an investor in determining which shares to buy. The higher value of a company will show the higher prosperity of the shareholders. A decline in share prices will result in a decrease in the prosperity of shareholders. The purpose of this study is to determine the factors that influence Price to Book Value fluctuations, in this study the variable factors are the Dividend Payout Ratio and Debt to Equity Ratio.The objects in this research are Dividend Payout Ratio, Debt To Equity Ratio and Price to Book Value in non-cyclical consumer sector companies listed on the Indonesian Stock Exchange. The number of samples in this study were 34 companies during the 2017-2019 period. The analysis technique in this study uses multiple regression analysis techniques, the tool is used in processing research data is SPSS.The results of this study indicate that the Dividend Payout Ratio has an effect on the Price To Book Value and the Debt To Equity Ratio has no effect on the Price To Book Value. Meanwhile, the Dividend Payout Ratio and Debt To Equity Ratio together have an effect on the Price To Book Value.